Allan Kaprow, Robert Smithson, and the Limits to Art - Ursprung, Philip (Book collections on Project MUSE., 2013)
"This innovative study of two of the most important artists of the twentieth century links the art practices of Allan Kaprow and Robert Smithson in their attempts to test the limits of art--both what it is and where it is. Ursprung provides a sophisticated yet accessible analysis, placing the two artists firmly in the art world of the 1960s as well as in the art historical discourse of the following decades. Although their practices were quite different, they both extended the studio and gallery into desert landscapes, abandoned warehouses, industrial sites, train stations, and other spaces. Ursprung bolsters his argument with substantial archival research and sociological and economic models of expansion and limits."--